2010
DOI: 10.1007/s12098-010-0313-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mycoplasma pneumoniae among HIV Infected Children

Abstract: The prevalence of M.pneumoniae infection among HIV seropositive children with respiratory tract infection in the present study is 32.2%. Early detection of M.pneumoniae infection and prompt initiation of therapy may halt further depletion of CD4 cells and rapid progression to AIDS in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Mycoplasmas tend to cause more severe and prolonged infections in the human immunodeficiency virus (HIV)-infected cases and other immunodeficient subjects. An Indian study by Nadagir et al 28 reported 32.2 per cent M. pneumoniae infection among HIV-seropositive children with respiratory tract infection. In these patients, early diagnosis and prompt initiation of treatment of M. pneumoniae infection may prevent CD4 cells depletion further and speedy progression to AIDS 28 .…”
Section: Mycoplasma Pneumoniae With Community-acquired Lowermentioning
confidence: 99%
See 1 more Smart Citation
“…Mycoplasmas tend to cause more severe and prolonged infections in the human immunodeficiency virus (HIV)-infected cases and other immunodeficient subjects. An Indian study by Nadagir et al 28 reported 32.2 per cent M. pneumoniae infection among HIV-seropositive children with respiratory tract infection. In these patients, early diagnosis and prompt initiation of treatment of M. pneumoniae infection may prevent CD4 cells depletion further and speedy progression to AIDS 28 .…”
Section: Mycoplasma Pneumoniae With Community-acquired Lowermentioning
confidence: 99%
“…An Indian study by Nadagir et al 28 reported 32.2 per cent M. pneumoniae infection among HIV-seropositive children with respiratory tract infection. In these patients, early diagnosis and prompt initiation of treatment of M. pneumoniae infection may prevent CD4 cells depletion further and speedy progression to AIDS 28 . Seroprevalence study among HIV-positive patients with pulmonary symptoms by Shankar et al 29 reported 21 per cent prevalence of M. pneumoniae IgM antibody by ELISA, and among 34 per cent of the cases screened, non-specific diagnosis was confirmed.…”
Section: Mycoplasma Pneumoniae With Community-acquired Lowermentioning
confidence: 99%
“…Among the seven patients with immunodeficiency and M. pneumoniae , there were three patients with AIDS, two cases of hypogammaglobulinemia, one case of agammaglobulinemia and one case of hyper-IgE syndrome. In a study in India that included 90 patients with AIDS, M. pneumoniae was detected in 32.3% of this population 47. A case of a patient with pneumonia due to M. pneumoniae who had hyper-IgM syndrome has been previously reported 48.…”
Section: Discussionmentioning
confidence: 97%
“…Nadagir et al observed a 32% prevalence of M . pneumoniae infections among HIV seropositive children with respiratory manifestations [ 21 ]. Some authors suggested that CD4 + T cell depletion associated with advanced HIV disease may enhance M .…”
Section: Combined Primary Immunodeficienciesmentioning
confidence: 99%